Online fuel consumption cost calculator (OFCCC) - Ahmad Solihin, Ahmad Syukri (2011)
Recently,fuel price becomes as hot topic and never ending issue especially the demand of fuel is very high.Malaysia Government has stood up in helping citizens by giving certain amount of money per vehicle owner to reduce their burden.However,the solution of reducing the total amount of fuel cost and consumption seems to be more helpful if the citizens can plan their fuel expenditure efficiently without unnecessary spend.Therefore,new software namely Online Fuel Consumption Cost Calculator (OFCCC) has been developed to help user plan and calculates the total amount of fuel cost for a car to travel based on the distance given,driving speed,weight capacity and current market fuel price cost. This software has been developed by using Microsoft Web Expression 2 and SQL Server database system.The result shows that the users can obtain a minimum cost towards the desired destination by using OFCCC.Keywords: OFCCC, database, software,fuel.